Organic-inorganic hybrid perovskite solar cells based on interface modification layer

By spin-coating trifluoromethylbenzene materials as an interface modification layer between the perovskite active layer and the hole transport layer of the perovskite solar cell, the problem of non-radiative recombination caused by interface defect states is solved and the photoelectric conversion is improved. efficiency and stability.

CN115394924BInactive Publication Date: 2025-01-24TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211068990.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing perovskite solar cells have many defect states at the interface between the perovskite active layer and the hole transport layer, resulting in non-radiative recombination and leakage current, reducing device performance and stability.

Method used

The triafluoro methyl benzene material is used as the interface modifier layer, and is applied between the active layer of the perovskite and the acupoint transmission layer.

Benefits of technology

A significant reduction of non -radiation composite, increasing the extraction and transportation of carriers, enhancing the photoelectric conversion efficiency and anti -humidity stability of the perovskite solar cell, and improved the photoelectric conversion efficiency to 21.6%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115394924B_ABST
    Figure CN115394924B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of perovskite solar cells, an organic-inorganic hybrid perovskite solar cell based on an interface modification layer, wherein the electron transport layer adopts a perovskite active layer, an interface modification layer formed by a trifluoromethylbenzene material is formed on the electron transport layer, and a hole transport layer composed of a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) layer is formed on the interface modification layer. The present invention can passivate the defects on the surface of the perovskite by spin-coating the trifluoromethylbenzene material at the interface between the perovskite active layer and the hole transport layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of perovskite solar cells, in particular to an organic-inorganic hybrid perovskite solar cell. Background Art

[0002] In recent years, the massive exploitation of traditional fossil energy sources such as coal, oil, and natural gas has led to serious energy crises and environmental pollution. In order to solve the increasingly severe energy and environmental problems, people have turned their attention to the development and utilization of new energy. As a clean and renewable energy source, solar energy has the advantages of being inexhaustible and inexhaustible. The most important thing is that it is environmentally friendly and is one of the best ways to solve the energy crisis and environmental pollution. Among the latest technologies, photovoltaic power generation is undoubtedly one of the most promising directions, and the development of low-cost, high-efficiency organic-inorganic hybrid perovskite solar cells has become a research hotspot in recent years.

[0003] Researchers will have ABX 3 The crystal structure of the general chemical formula is collectively referred to as perovskite. Organic-inorganic hybrid perovskites have the advantages of high carrier mobility, narrow optical band gap, and easy solution processing. They are the dominant type of perovskites at present, so solar cells prepared with them have been widely studied. Among them, for planar heterojunction perovskite solar cells with an upright structure, on the one hand, there are many defect states at the interface between the perovskite active layer and the hole transport layer. The presence of these defects will cause serious non-radiative recombination, resulting in the existence of leakage current, thereby reducing the device performance of the perovskite solar cell. On the other hand, the stability of perovskite materials is poor, they are sensitive to water and oxygen, and they are easy to decompose. The problems at the interface between the perovskite layer and the transport layer will also restrict the stability of perovskite solar cells. Therefore, the development of high-efficiency, low-cost, and stable perovskite solar cells is very important for future commercial development. Summary of the invention

[0004] The technical problem to be solved by the present invention is: how to reduce the defect state at the interface between the perovskite and the hole transport layer by a suitable interface modification material and improve the carrier transport performance.

[0005] The technical solution adopted by the present invention is: an organic-inorganic hybrid perovskite solar cell based on an interface modification layer, wherein the electron transport layer adopts a perovskite active layer, above the electron transport layer is an interface modification layer formed by a trifluoromethylbenzene material, and above the interface modification layer is a hole transport layer composed of a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) layer.

[0006] The perovskite active layer is FA x MA 1-xPbInBr3-nPerovskite film or MAPbI 3 The film has a thickness of 550-600 nm for the perovskite active layer, x is a positive number less than 1, and n is a positive number less than 3; the trifluoromethylbenzene material is a mixture of one or more of 4-amino-2-trifluoromethylbenzonitrile (ATMB), 4-bromo-3-(trifluoromethyl)aniline, and 4-chloro-2-trifluoromethylbenzonitrile.

[0007] The FA x MA 1-xPbInBr3-n The method for preparing the perovskite film comprises the following steps

[0008] S311、PbI 2 ) is dissolved in a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to form a golden solution called lead iodide (PbI 2 ) Precursor fluid;

[0009] S312, dissolving formamidine ammonium iodide (FAI), methyl ammonium bromide (MABr), and methyl ammonium chloride (MACl) in an isopropyl alcohol (IPA) solvent at a mass ratio of 10:1:1 to form an organic cationic solution, wherein the concentration of formamidine ammonium iodide (FAI) is 60 mg / mL; S313, in a nitrogen environment, the ambient temperature is maintained at 15°C-25°C, and the lead iodide precursor solution is statically spin-coated on the electron transport layer by a solution spin coating method, the spin coating rate is 1500-1800 rpm, the spin coating time is 30-40 s, and after the spin coating is completed, annealing is performed at 70°C in a nitrogen environment for 1 min to form PbI 2 Precursor film; then, in a nitrogen environment, the PbI 2 The precursor film is statically spin-coated with an organic cationic solution at a spin-coating rate of 1600-2000 rpm for 30-40 s. After spin-coating, the film is transferred to air and annealed on a hot stage at 115°C for 25-30 min.

[0010] The MAPbI 3 The method for preparing the film comprises the following steps:

[0011] S321, N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) were mixed to prepare a mixed solvent with a volume ratio of 9:1, and then lead iodide (PbI 2 ) and methylammonium iodide (MAI) are dissolved in a mixed solvent to form a mixed solution with a lead iodide concentration of 599.3 mg / mL and a methylammonium iodide concentration of 44.7 mg / mL;

[0012] S322, using a spin coating method, spin coating the mixed solution prepared in step S321 on the electron transport layer, the spin coating speed is 6000 rpm, the spin coating time is 15 s, to form a first thin film;

[0013] S322, spin-coat a 35 mg / mL MAI solution in isopropanol on the first film at a rate of 4000 rpm for 30-45 s, then transfer to air and anneal at 100 °C for 30 min to prepare MAPbI 3 Perovskite thin films.

[0014] The preparation method of the interface modification layer is as follows: dissolving a trifluoromethylbenzene material in a chlorobenzene solution to form a trifluoromethylbenzene material solution with a mass concentration of 1 mg / mL, and then using a solution spin coating method at a spin coating rate of 4000 rpm for 30-40 seconds, annealing on a hot stage at 100°C for 5 minutes to obtain an interface modification layer with a thickness of 1-5 nm.

[0015] The preparation of the hole transport layer includes the following steps:

[0016] S51. Dissolve 72.3 mg of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) in 1 mL of chlorobenzene, stir and shake thoroughly to obtain a chlorobenzene solution of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD);

[0017] S52, dissolving 520 mg of lithium bis(trifluoromethanesulfonic acid) amide in 1 mL of acetonitrile solution, stirring and shaking thoroughly to obtain lithium bis(trifluoromethanesulfonic acid) amide acetonitrile solution;

[0018] S53, add 18 μL of lithium bis(trifluoromethanesulfonic acid) imide acetonitrile solution and 29 μL of 4-tert-butylpyridine (TBP) to the prepared 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution, stir and shake thoroughly to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) mixed solution;

[0019] S54. Spin-coat a mixed solution of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) on the surface of the interface modification layer to prepare a hole transport layer with a thickness of 150-180 nm.

[0020] The organic-inorganic hybrid perovskite solar cell consists of a transparent conductive glass substrate, SnO 2 An electron transport layer composed of a layer, an electron transport layer composed of a perovskite active layer, an interface modification layer formed of a trifluoromethylbenzene material, and a hole transport layer composed of a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) layer.

[0021] The preparation method of the electron transport layer is to prepare SnO 2 Prepare SnO with water in a volume ratio of 1:4 2 The aqueous solution was spin-coated on a transparent conductive glass substrate at a rate of 4000 rpm for 30-40 s. After the spin coating was completed, the substrate was heat-treated in air for 25-30 min at a temperature of 150 °C. The electron transport layer SnO 2 The thickness is 30-40 nm.

[0022] The beneficial effects of the present invention are as follows: a layer of trifluoromethylbenzene material is spin-coated at the interface between the perovskite active layer and the hole transport layer. First, the defect states on the surface of the perovskite can be passivated, thereby reducing non-radiative recombination, reducing leakage current, and making the carriers at the interface more effectively extracted and transported, so that the photoelectric conversion efficiency of the perovskite solar cell is improved. Second, many unstable factors (moisture, oxygen and ultraviolet rays) also come from these defects, and the presence of the F-containing passivation layer can protect the perovskite, thereby enhancing its anti-humidity stability. Third, spin-coating a layer of trifluoromethylbenzene material can also improve the interface contact between the perovskite and the hole transport layer. Better interface contact performance is very important for improving the photoelectric conversion efficiency and stability of the perovskite solar cell, so the presence of the trifluoromethylbenzene passivation layer material can improve the photoelectric conversion efficiency and stability of the perovskite solar cell.

[0023] The present invention proposes to spin-coat a trifluoromethylbenzene material at the interface between the perovskite active layer and the hole transport layer, so that the photoelectric conversion efficiency and stability of the perovskite solar cell are simultaneously improved, and the photoelectric conversion efficiency of the NIP-type organic-inorganic hybrid perovskite solar cell is increased to 21.6%. The present invention provides an effective solution for the research and development of low-cost, high-efficiency, and stable perovskite solar cells.

[0024] The present invention can passivate the defects on the surface of perovskite by spin coating trifluoromethylbenzene materials at the interface between the perovskite active layer and the hole transport layer, significantly reduce the non-radiative recombination of perovskite solar cells, improve the photoelectric conversion efficiency of perovskite solar cells, and improve its water-oxygen stability, so that the photoelectric conversion efficiency and stability of perovskite solar cells are simultaneously improved, and the photoelectric conversion efficiency of perovskite solar cells in the NIP system is increased from 19.4% to 21.6%. The present invention provides an effective solution for the research and development of low-cost, high-efficiency, and stable perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a structural diagram of a perovskite solar cell prepared in an embodiment of the present invention;

[0026] Figure 2 is an atomic force microscope image, where Figure 2 (a) is an atomic force microscope image of a perovskite film without a passivation layer. Figure 2 (b) is an atomic force microscopy image of the perovskite film modified with an ATMB interface passivation layer;

[0027] Figure 3 is the steady-state fluorescence spectrum, where Figure 3 Curve a in the figure is the steady-state fluorescence spectrum of the perovskite film without passivation layer modification. Figure 3 Curve b in the figure is the steady-state fluorescence spectrum of the perovskite film modified with the ATMB interface passivation layer;

[0028] Figure 4 is the JV curve of the perovskite solar cell, where Figure 4 Curve a in the figure is the JV curve of the perovskite solar cell without interface modification layer. Figure 4 Curve b in the figure is the JV curve of the perovskite solar cell based on the ATMB interface modification layer. DETAILED DESCRIPTION Example 1

[0029] like Figure 1 As shown, an organic-inorganic hybrid perovskite solar cell based on an interface modification layer has a planar heterojunction upright structure: from bottom to top, ITO / SnO 2 / Perovskite active layer / ATMB / Spiro-OMeTAD / Ag.

[0030] The specific preparation process of organic-inorganic hybrid perovskite solar cells based on interface modification layer is as follows

[0031] S1, pretreatment of the ITO conductive glass substrate: the method is to clean and dry the ITO conductive glass substrate, cool it to room temperature and then ozone treat the ITO conductive glass substrate for 15 min;

[0032] S2, electron transport layer SnO 2 The film was formed by solution spin coating and then thermal annealing in air. The spin coating rate was 4000 rpm, the spin coating time was 30 s, the heating temperature was 150 ° C, the heating time was 30 min, and the SnO 2 The aqueous solution is composed of SnO 2 It is prepared with water in a volume ratio of 1:4.

[0033] S3, Preparation of FA x MA 1-xPbInBr3-n The perovskite film is made by a two-step process. First, lead iodide (PbI 2 ) 1.3M, and then dissolved in a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), the volume ratio of the mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) was 19:1, and the ITO / SnO 2 Static spin coating of PbI on substrate 2 The precursor solution was spin-coated at a rate of 1700 rpm for 30 s. After the spin coating was completed, the product was annealed at 70 °C in a nitrogen environment for 1 min to form PbI 2 Precursor film, then formamidine iodide (FAI), methyl ammonium bromide (MABr), and methyl ammonium chloride (MACl) were dissolved in isopropyl alcohol (IPA) solvent at a mass ratio of 10:1:1, and the concentration of formamidine iodide (FAI) was 60 mg / mL. The resulting organic cation solution was added dropwise to lead iodide (PbI 2 ) film surface, the spin coating rate was 1700 rpm, the spin coating time was 30 s, and after the spin coating was completed, it was transferred to the air and annealed on a hot plate at 115°C for 30 min. x MA 1-xPbInBr3-n The perovskite film is completed.

[0034] S4, ATMB interface modification layer is prepared by dissolving ATMB in chlorobenzene solution with a concentration of 1 mg / mL and forming the film by solution spin coating with a spin coating rate of 4000 rpm, a spin coating time of 30 s, a heating temperature of 100 °C, and a heating time of 5 min.

[0035] S5, Spiro-OMeTAD mixed solution is prepared by dissolving 72.3 mg of Spiro-OMeTAD in 1 mL of chlorobenzene, stirring and shaking thoroughly, then taking 18 μL of bis(trifluoromethanesulfonic acid) imide lithium acetonitrile solution (520 mg / mL) and 29 μL of 4-tert-butylpyridine (TBP) and adding them, stirring and shaking thoroughly. The film is formed by solution spin coating, the spin coating rate is 4000 rpm, and the spin coating time is 30 s.

[0036] S6, the cathode material is composed of silver (Ag), and the film is formed by vacuum thermal evaporation method, the film thickness is 100 nm, and the evaporation rate is 0.5 nm / s.

[0037] Finally, an organic-inorganic hybrid perovskite solar cell based on ATMB interface modification was obtained.

[0038] The test results are as follows:

[0039] like Figure 2 (a) is an atomic force microscope image of a perovskite film without a passivation layer. Figure 2 (b) is an atomic force microscopy image of the perovskite film modified with the ATMB interface passivation layer. The film modified with the ATMB interface passivation layer is denser and smoother.

[0040] Figure 3 Curve a in the figure is the steady-state fluorescence spectrum of the perovskite film without passivation layer modification. Figure 3 Curve b in the figure is the steady-state fluorescence spectrum of the perovskite film modified with the ATMB interface passivation layer. The steady-state fluorescence spectrum of the perovskite film modified with the ATMB interface passivation layer is enhanced.

[0041] Figure 4 Curve a in the figure is the JV curve of the perovskite solar cell without interface modification layer. Figure 4 Curve b in the figure is the JV curve of the perovskite solar cell based on the ATMB interface modification layer. The photoelectric conversion efficiency of the device is improved after ATMB modification.

[0042] The present invention proposes to introduce trifluoromethylbenzene materials into the interface between perovskite and hole transport layer (Spiro-OMeTAD) as a passivation layer for modification, thereby achieving (1) more effective passivation of interface defects and significantly improving carrier extraction and transport. (2) Improved humidity stability of perovskite solar cells. (3) Improved interface contact between perovskite and hole transport layer. The photoelectric conversion efficiency of perovskite solar cells modified with ATMB interface passivation layer is greatly improved. Example 2

[0043] In this embodiment, a method for preparing an organic-inorganic hybrid perovskite solar cell modified with 4-bromo-3-(trifluoromethyl)aniline is prepared. The difference between this comparative example and comparative example 1 is that in the above step S2, the 4-amino-2-trifluoromethylbenzonitrile (ATMB) used is replaced by 4-bromo-3-(trifluoromethyl)aniline, and the formula replacement concentration is the same as that of 4-amino-2-trifluoromethylbenzonitrile, and the other steps are basically the same as those in comparative example 1, which will not be repeated here. Example 3

[0044] In this example, a method for preparing a perovskite solar cell based on 4-amino-2-trifluoromethylbenzonitrile (ATMB) interface modification is prepared. The difference between this comparative example and comparative example 1 is that in the above step S3, the perovskite film used is replaced by MAPbI 3 The film was prepared by mixing N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) into a mixed solvent with a volume ratio of about 9:1, and then lead iodide (PbI 2 ) and methyl ammonium iodide (MAI) were dissolved in a mixed solvent to form a mixed solution with a lead iodide concentration of 599.3 mg / mL and a methyl ammonium iodide concentration of 44.7 mg / mL. The perovskite film was prepared by spin coating. The first step was to spin coat at a speed of 6000 rpm for 15 s to form the first film. Then, a 35 mg / mL MAI solution in isopropanol was spin coated on the first film to form the second film. The spin coating speed was 4000 rpm for 30-45 s. Then, the film was transferred to air and annealed at 100 °C for 30 min to form MAPbI 3 Perovskite thin films.

[0045] The innovation of the present invention lies in the use of trifluoromethylbenzene materials to spin-coat the interface between the perovskite active layer and the hole transport layer. First, it can passivate the defect states on the surface of the perovskite, thereby reducing non-radiative recombination, reducing leakage current, and making the carriers at the interface more effectively extracted and transported, so that the photoelectric conversion efficiency of the perovskite solar cell is improved. Second, many unstable factors (moisture, oxygen and ultraviolet rays) also come from these defects, and the presence of the F-containing passivation layer can protect the perovskite and enhance its humidity resistance stability. Third, spin-coating a layer of trifluoromethylbenzene materials can also improve the interface contact between the perovskite and the hole transport layer. Better interface contact performance is very important for improving the photoelectric conversion efficiency and stability of perovskite solar cells. Therefore, the presence of trifluoromethylbenzene passivation layer materials can improve the photoelectric conversion efficiency and stability of perovskite solar cells. The beneficial effects produced are such as Figure 2 (a) is an atomic force microscope image of a perovskite film without a passivation layer. Figure 2(b) is an atomic force microscopy image of the perovskite film modified with the ATMB interface passivation layer. The film modified with the ATMB interface passivation layer is denser and smoother. Figure 3 Curve a in the figure is the steady-state fluorescence spectrum of the perovskite film without passivation layer modification. Figure 3 Curve b in the figure is the steady-state fluorescence spectrum of the perovskite film modified with the ATMB interface passivation layer. The steady-state fluorescence spectrum of the perovskite film modified with the ATMB interface passivation layer is enhanced and the defect state density is reduced. Figure 4 Curve a in the figure is the JV curve of the perovskite solar cell without interface modification layer. Figure 4 Curve b in the figure is the JV curve of the perovskite solar cell based on the ATMB interface modification layer. After ATMB modification, the photoelectric conversion efficiency of the device increased from 19.4% to 21.6%.

[0046] The above descriptions are only individual embodiments of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principles of the present invention. These improvements are considered to be within the protection scope of the present invention.

Claims

1. An organic-inorganic hybrid perovskite solar cell based on an interface modification layer, characterized in that: The electron transport layer adopts a perovskite active layer, and the interface modification layer formed by trifluoromethylbenzene materials is above the electron transport layer, and the hole transport layer is composed of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene layer above the interface modification layer; the perovskite active layer is FA x MA 1-x PbI n Br 3-n Perovskite film or MAPbI3 film, the thickness of the perovskite active layer is 550-600 nm, x is a positive number less than 1, and n is a positive number less than 3; the trifluoromethylbenzene material is a mixture of one or more of 4-amino-2-trifluoromethylbenzonitrile and 4-chloro-2-trifluoromethylbenzonitrile.

2. The organic-inorganic hybrid perovskite solar cell based on an interface modification layer according to claim 1, characterized in that: The FA x MA 1-x PbI n Br 3-n The method for preparing the perovskite film comprises the following steps S311, dissolving lead iodide in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide to form a golden solution, referred to as a lead iodide precursor solution; S312. Dissolve formamidine ammonium iodide, methyl ammonium bromide and methyl ammonium chloride in an isopropanol solvent at a mass ratio of 10:1:1 to form an organic cationic solution, and the concentration of formamidine ammonium iodide is 60 mg / mL. S313. In a nitrogen environment, the ambient temperature is maintained at 15℃-25℃, and the lead iodide precursor solution is statically spin-coated on the electron transport layer by solution spin coating. The spin coating rate is 1500-1800 rpm, and the spin coating time is 30-40 s. After the spin coating is completed, annealing is performed at 70℃ in a nitrogen environment for 1 min to form a PbI2 precursor film. Then, in a nitrogen environment, the organic cationic solution is statically spin-coated on the PbI2 precursor film by solution spin coating. The spin coating rate is 1600-2000 rpm, and the spin coating time is 30-40 s. After the spin coating is completed, transfer it to air and anneal on a 115℃ hot stage for 25-30 min.

3. The organic-inorganic hybrid perovskite solar cell based on an interface modification layer according to claim 1, characterized in that: The preparation method of the MAPbI3 film comprises the following steps: S321, mixing N,N-dimethylformamide and dimethyl sulfoxide to form a mixed solvent in a volume ratio of 9:1, and then dissolving lead iodide and methyl ammonium iodide in the mixed solvent to form a mixed solution with a lead iodide concentration of 599.3 mg / mL and a methyl ammonium iodide concentration of 44.7 mg / mL; S322, using a spin coating method, spin coating the mixed solution prepared in step S321 on the electron transport layer, the spin coating speed is 6000 rpm, the spin coating time is 15 s, to form a first thin film; S322. Spin coat a 35 mg / mL MAI solution in isopropanol on the first film at a rate of 4000 rpm for 30-45 s, then transfer to air and anneal at 100 °C for 30 min to form a MAPbI3 perovskite film.

4. The organic-inorganic hybrid perovskite solar cell based on an interface modification layer according to claim 1, characterized in that: The preparation method of the interface modification layer is as follows: dissolving a trifluoromethylbenzene material in a chlorobenzene solution to form a trifluoromethylbenzene material solution with a mass concentration of 1 mg / mL, and then using a solution spin coating method at a spin coating rate of 4000 rpm for 30-40 seconds, annealing on a hot stage at 100°C for 5 minutes to obtain an interface modification layer with a thickness of 1-5 nm.

5. The organic-inorganic hybrid perovskite solar cell based on an interface modification layer according to claim 1, characterized in that: The preparation of the hole transport layer includes the following steps: S51, dissolving 72.3 mg of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene in 1 mL of chlorobenzene, stirring and shaking thoroughly to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution; S52, dissolving 520 mg of lithium bis(trifluoromethanesulfonic acid) amide in 1 mL of acetonitrile solution, stirring and shaking thoroughly to obtain lithium bis(trifluoromethanesulfonic acid) amide acetonitrile solution; S53, take 18 μL of lithium bis(trifluoromethanesulfonic acid) imide acetonitrile solution and 29 μL of 4-tert-butylpyridine, add them to the prepared 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene chlorobenzene solution, stir and shake thoroughly to obtain a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene mixed solution; S54. Spin-coat a mixed solution of 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene on the surface of the interface modification layer to obtain a hole transport layer with a thickness of 150-180 nm.

6. The organic-inorganic hybrid perovskite solar cell based on an interface modification layer according to claim 1, characterized in that: The organic-inorganic hybrid perovskite solar cell comprises, from bottom to top, a transparent conductive glass substrate, an electron transport layer composed of a SnO2 layer, an electron transport layer composed of a perovskite active layer, an interface modification layer formed of a trifluoromethylbenzene material, and a hole transport layer composed of a 2,2,7,7′-tetrakis[N,N′-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene layer.

7. An organic-inorganic hybrid perovskite solar cell based on an interface modification layer according to claim 6, characterized in that: The preparation method of the electron transport layer is as follows: SnO2 and water are configured into a SnO2 aqueous solution in a volume ratio of 1:4, and the solution is spin-coated on a transparent conductive glass substrate at a rate of 4000 rpm for 30-40 s. After the spin coating is completed, the solution is heat-treated in air for 25-30 min at a heat treatment temperature of 150°C. The thickness of the electron transport layer SnO2 formed after the heat treatment is 30-40 nm.